Silkville, Franklin County - Angermayer, Lauren (Kansas State University, The Chapman Center for Rural Studies, 2015)
Silkville Ranch was an experimental socialist community founded by Ernest de Boissiere in Franklin County, Williamsburg Township. Although the experiment failed due to financial challenges, Silkville persists as a ranch. This study includes interviews, an unpublished history, and early and later pictures of the ranch.
Lauren Angermayer, “Silkville, Franklin County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/156.
Keywords: Franklin County; Bichelmeyer; Odd Fellows Lodge; Roger Williams University; Silkville; Williamsburg